2022
DOI: 10.1038/s41597-022-01341-2
|View full text |Cite
|
Sign up to set email alerts
|

Multi sequence average templates for aging and neurodegenerative disease populations

Abstract: Magnetic resonance image (MRI) processing pipelines use average templates to enable standardization of individual MRIs in a common space. MNI-ICBM152 is currently used as the standard template by most MRI processing tools. However, MNI-ICBM152 represents an average of 152 healthy young adult brains and is vastly different from brains of patients with neurodegenerative diseases. In those populations, extensive atrophy might cause inevitable registration errors when using an average template of young healthy ind… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…We used the MNI-152 brain as a commonly utilized template, but there may be closer matching composite MRI scans depending on the population of interest. For instance, if a researcher wanted to investigate the group-level E-fields in an aging population could consider using more specific age-matched ( Fillmore et al, 2015 ) or diagnosis-matched ( Dadar et al, 2022 ) templates for potentially more accurate simulations. While we used bilateral electrode placements (i.e., C3-C4 and F3-F4) instead of other common electrode placements (e.g., C3-SO and F3-SO), prior large-scale findings have shown that there are no significant differences in E-field magnitudes between C3-C4 and C3-SO ( Caulfield and George, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…We used the MNI-152 brain as a commonly utilized template, but there may be closer matching composite MRI scans depending on the population of interest. For instance, if a researcher wanted to investigate the group-level E-fields in an aging population could consider using more specific age-matched ( Fillmore et al, 2015 ) or diagnosis-matched ( Dadar et al, 2022 ) templates for potentially more accurate simulations. While we used bilateral electrode placements (i.e., C3-C4 and F3-F4) instead of other common electrode placements (e.g., C3-SO and F3-SO), prior large-scale findings have shown that there are no significant differences in E-field magnitudes between C3-C4 and C3-SO ( Caulfield and George, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…missing slices, incomplete field of view), as well as linear and nonlinear alignment of the images with the outline of the MNI-ICBM152-2009c average template (Manera et al, 2020). Registration QC was conducted following the protocols outlined in Dadar et al 2018, 2022 (Dadar et al, 2022, 2018). Each image in the two datasets underwent these steps, and quality ratings were recorded.…”
Section: Methodsmentioning
confidence: 99%
“…To facilitate comparisons across subjects, data from each subject should be registered to a template. Moreover, templates based on multiple subjects are optimal for group-level analyses because they possess features that are more representative of the population's "average" brain anatomy which offers higher cross-subject validity (Dadar et al, 2022;Evans et al, 2012;Fonov et al, 2011).…”
Section: Introductionmentioning
confidence: 99%